Performance analysis of handover in LTE (long term evolution) femtocell network / Mohd Hafiz Abu Bakar - Abu Bakar, Mohd Hafiz (2014)
The latest technology in wireless communication system is Long Term Evolotion (LTE) Femtocell with one of the purpose of this technology is to enhance indoor coverage by using 'plug and play' approach by the user as the operation of this technology. LTE technology are expected to conquer the telecommunication industry services of mobile network as it upgraded from circuit switches to packet switches and also moving forward from voice to data. This technology was said to give lots of benefit beyond 3G mobile towards system operator and the benefit itself in terms of economy. With the expectation to provide higher throughput and lower transmission latency to the mobile user, the LTE technology is known as technologies towards next generation mobile broadband standard and Femtocell is one of network that having a lot of benefit and advantages for users and operators. Handover for emerging technologies can be define by this function which also let network operators gets some benefit from it by adding to its value [1]. This study is on Performance Analysis of Handover in LTE (Long Term Evolution) Femtocell. In order to analyze the handover performance in LTE, four scenarios are investigated with three Femtocells (without handover), with three Femtocells (with handover), with five Femtocells (without handover) and with five Femtocells (with handover). This paper will explore the entire scenario by using LTE-Sim network simulator. This paper begins with a brief history and an overview of LTE (Long Term Evolution) technologies.